2011
DOI: 10.1080/08870441003703218
|View full text |Cite
|
Sign up to set email alerts
|

Fruitful plans: Adding targeted mental imagery to implementation intentions increases fruit consumption

Abstract: Forming implementation intentions ('If I encounter situation X, then I will perform behaviour Y!') increases the probability of carrying out goals. This study tested the hypothesis that mental imagery targeting key elements of implementation intentions further increases goal achievement. The residents of a student residence were assigned the goal of consuming extra portions of fruit every day for 7 days and randomly assigned to one of four conditions: control (active rehearsal), implementation intentions, goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
5
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 32 publications
5
85
5
2
Order By: Relevance
“…It was predicted that although visualisation would be more effective when it was combined with a health message, it would still be effective without the presentation of a health message. This contrasts Visualisation for increasing health intentions 18 with previous research finding beneficial effects of visualisation even in the absence of a message (e.g., Knäuper et al, 2011;Ouellette et al, 2005). It might be that the effects of visualisation differ according to the particular health behaviour being visualised, their baseline motivation to engage in that particular behaviour, or indeed the difficulty of the visualised behaviour.…”
Section: Discussioncontrasting
confidence: 50%
“…It was predicted that although visualisation would be more effective when it was combined with a health message, it would still be effective without the presentation of a health message. This contrasts Visualisation for increasing health intentions 18 with previous research finding beneficial effects of visualisation even in the absence of a message (e.g., Knäuper et al, 2011;Ouellette et al, 2005). It might be that the effects of visualisation differ according to the particular health behaviour being visualised, their baseline motivation to engage in that particular behaviour, or indeed the difficulty of the visualised behaviour.…”
Section: Discussioncontrasting
confidence: 50%
“…Past research has demonstrated that visualising oneself engaging in a behaviour increases the likelihood of actually engaging in that behaviour in the future (e.g., Gregory, Cialdini & Carpenter, 1982;Knäuper et al, 2011). A growing body of evidence highlights the role of perspective used in visual imagery.…”
Section: Bigger-picture Thinking For Behaviour Changementioning
confidence: 99%
“…Obesity and overweight are multifaceted issues with a wide range of determining factors, and therefore behaviour change scientists should aim to create interventions that tackle not just one, but multiple predictive behaviours such as exercise and eating habits. One strategy that helps target these predictive behaviors is to visualize oneself in engaging them (e.g., Knäuper et al, 2011). Further, research has shown that visualising behaviours using the more distanced perspective of an observer helps to "see the bigger picture" and thereby link the visualised behaviour to broader goals (Vasquez & Buehler, 2007;Libby & Eibach, 2011;Kross & Grossmann, 2012), with the potential to result in behaviour change across multiple domains.…”
Section: Bigger-picture Thinking For Behaviour Changementioning
confidence: 99%
“…Separate lines of inquiry support the use of guided imagery to enhance physical activity, improve diet, and quit smoking [47][48][49][50][51]. Guided imagery is an easily learned cognitive technique in which the user imagines detailed engagement in an activity and involves their emotions and all the senses [52].…”
Section: Introductionmentioning
confidence: 99%